Sistem Pendukung Keputusan dalam Penentuan Beasiswa dengan Logika Fuzzy Tsukamoto di STMIK Sumedang - Dody Herdiana; Dwi Yuniarto; Esa Firmansyah (Journal of Information Technology, 2019)
STMIK Sumedang is one of the high schools that has a scholarship system for Academic Achievement Improvement (PPA). Where PPA or Academic Achievement Improvement Scholarships are scholarships that are given to increase equity and learning opportunities like students who have academic achievements. Based on data collected, the number of scholarship applications is quite large, with various criteria students appear to have difficulties in determining the winners of student scholarships with almost the same number of indicators and criteria. On the basis of these findings, it is necessary to have a system that is able to help determine scholarship recipients that fit the criteria specified. The results achieved in the form of Decision Support Systems in Determining Scholarships are expected to help STMIK Sumedang in making scholarship decisions.